2022
DOI: 10.1021/acscatal.2c05554
|View full text |Cite
|
Sign up to set email alerts
|

Metallaphotoredox Decarboxylative Arylation of Natural Amino Acids via an Elusive Mechanistic Pathway

Abstract: The merger of photoredox and nickel catalysis for the decarboxylative arylation of carboxylic acids has evolved into an effective strategy to forge C–C bonds from readily available feedstock. Despite its rapid industrial adoption, the mechanism of this dual-catalyzed cross-coupling reaction has remained unclear and under-studied. Here, we propose an alternative mechanism for the photoredox–Ni dual-catalyzed decarboxylative arylation of α-amino acids based on control experiments with NiIIArBr complexes, cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…To further advance metallaphotoredox C(sp 2 )−C(sp 3 ) crosscoupling, broaden its industrial applicability, and gain a better understanding of its mechanism, we reinvestigated the decarboxylative cross-coupling reaction of α-amino acids with aryl halides (Figure 2A-C). 2 This reaction is desirable in medicinal chemistry because it uses abundant and cheap αamino acid feedstocks as diverse alkyl inputs. The optimization of the reported metallaphotoredox conditions resulted in the identification of a new set of conditions comprising of cheap and simple Ni catalyst system (H 2 O) 6 Ni(BF 4 ) 2 and bipyridine (bpy).…”
Section: C(sp 2 )−C(sp 3 ) Decarboxylative Arylationmentioning
confidence: 99%
See 2 more Smart Citations
“…To further advance metallaphotoredox C(sp 2 )−C(sp 3 ) crosscoupling, broaden its industrial applicability, and gain a better understanding of its mechanism, we reinvestigated the decarboxylative cross-coupling reaction of α-amino acids with aryl halides (Figure 2A-C). 2 This reaction is desirable in medicinal chemistry because it uses abundant and cheap αamino acid feedstocks as diverse alkyl inputs. The optimization of the reported metallaphotoredox conditions resulted in the identification of a new set of conditions comprising of cheap and simple Ni catalyst system (H 2 O) 6 Ni(BF 4 ) 2 and bipyridine (bpy).…”
Section: C(sp 2 )−C(sp 3 ) Decarboxylative Arylationmentioning
confidence: 99%
“…ACS Catal . 2023 , 13 , 647–658 Mechanistic investigation and elucidation of an alternative Ni 0/II/I/II pathway accessible for metallaphotoredox decarboxylative cross-coupling reactions . Palkowitz, M. D.; Laudadio, G.; Kolb, S.; Choi, J.; Oderinde, M. S.; Ewing, T. E.-H.; Bolduc, P. N.; Chen, T.; Zhang, H.; Cheng, P. T. W.; Zhang, B.; Mandler, M. D.; Blasczak, V. D.; Richter, J. M.; Collins, M. R.; Schioldager, R. L.; Bravo, M.; Dhar, T. G. M.; Vokits, B.; Zhu, Y.; Echeverria, P.-G.; Poss, M. A.; Shaw, S. A.; Clementson, S.; Petersen, N. N.; Mykhailiuk, P. K.; Baran, P. S. Overcoming Limitations in Decarboxylative Arylation via Ag–Ni Electrocatalysis. J.…”
Section: Key Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids, being versatile building blocks and widely occurring organic compounds in nature, are indispensable for life. In recent decades, significant efforts have been dedicated to the decarboxylation of amino acids for the purpose of introducing functional groups and obtaining bioactive molecules. Among them, oxidative decarboxylation catalyzed by various transition-metal or metal-free catalysts has been regarded as a classic pathway. However, the presence of stoichiometric chemical oxidants is inevitable in these conventional decarboxylation strategies. Consequently, the utilization of photochemistry and electrochemistry , has sparked significant interest in developing a variety of decarboxylative functionalization methods for amino acids (Scheme a, left).…”
Section: Introductionmentioning
confidence: 99%
“…Seeking to address this gap in the synthetic literature and develop a step-economical approach for the construction of α-oxy-arylated morpholines, we turned to metallaphotoredox-mediated decarboxylative cross-couplings of carboxylic acids and aryl halides as a possible solution. , While the large body of work on carboxylic acids in metallaphotoredox chemistry affords entry to an array of diversified scaffolds, there is a striking lack of systematic study on α-oxy acids, in comparison to the much more well-studied α-amino and alkyl acid classes. , At the time our study concluded, to our knowledge, there had been no reported methods in the chemical literature that allow for direct use of commercially available α-oxy morpholine acids in decarboxylative metallaphotoredox cross-coupling. , …”
mentioning
confidence: 99%